Developing strategic key performance indicators using the balanced scorecard framework: the experience of Malaysian listed companies - Noorhayati Mansor; Asniati Bahari; Jainurin Justine @ Abdul Aziz (Universiti Malaysia Sabah, 2006)
no abstract